Data and sample sharing as an enabler for large-scale biomarker research and development: The EPND perspective - Bose, Niranjan; Brookes, Anthony J.; Scordis, Phil; Visser, Pieter Jelle (Frontiers in Neurology, 2022)
Biomarker discovery, development, and validation are reliant on large-scale analyses of high-quality samples and data. Significant quantities of data and samples have been generated by European studies on Alzheimer's disease (AD) and other neurodegenerative diseases (NDD), representing a valuable resource for developing biomarkers to support early detection of disease, treatment monitoring, and patient stratification. However, discovery, access, and sharing of data and samples are hindered both by silos that limit collaboration, and by the array of complex requirements for secure, legal, and ethical sharing. Here, we examine key challenges currently hampering large-scale biomarker research, and outline how the European Platform for Neurodegenerative Diseases (EPND) plans to address them. The first challenge is a fragmented landscape filled with technical barriers that make it difficult to discover and access high-quality samples and data in one location. A second challenge is the complex array of regulations that must be navigated by researchers when sharing data and samples, to ensure legal and ethical compliance. Another challenge is the lack of broad-scale collaboration and opportunities to facilitate partnerships between data and sample contributors and researchers, in addition to a lack of regulatory engagement early in the research process to enable biomarker validation. A further challenge is the need for projects to remain sustainable beyond initial funding periods, ensuring data and samples are shared, thereby driving further research and innovation. In addressing these challenges, EPND will enable an environment of faster and more disruptive research on diagnostics and disease-modifying therapies for AD and other NDD.